2005
DOI: 10.1097/01202412-200501000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome in children

Abstract: Carpal tunnel syndrome is a condition rarely encountered in infants. We describe five patients with nine involved hands. One was reported earlier. In three cases the cause of carpal tunnel syndrome is a storage disease: one girl with mucolipidosis type III and a boy and a girl with mucopolysaccharidosis type I. The fourth case is a girl presenting with unilateral macrodactyly of the right third and fourth digits. The last case involves a boy with familial carpal tunnel syndrome. We briefly discuss these patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
1
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 30 publications
0
61
1
8
Order By: Relevance
“…The tumor may present as a palpable mass of variable size or as spontaneous localized pain; although numbness and muscle wasting may occur, motor or sensory deficits are rare [23,42]. A few cases of carpal tunnel syndrome attributable to a hemangioma of the median nerve have been described as well [6,37]. In our case, the patient presented with a painless, gradually increasing mass and numbness at the median nerve distribution.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The tumor may present as a palpable mass of variable size or as spontaneous localized pain; although numbness and muscle wasting may occur, motor or sensory deficits are rare [23,42]. A few cases of carpal tunnel syndrome attributable to a hemangioma of the median nerve have been described as well [6,37]. In our case, the patient presented with a painless, gradually increasing mass and numbness at the median nerve distribution.…”
Section: Discussionmentioning
confidence: 69%
“…Current treatment for intraneural hemangioma includes intraneural or intrafascicular microdissection with preservation of the continuity of the nerve [2,3,6,23,37]. Nerve grafting may be required if the tumor cannot be resected free of a motor nerve.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important in children, who may not complain of symptoms but have electrodiagnostic evidence of nerve damage [1,4,8,9,33]. Patient #3's initially unilateral presentation, but ultimate need for contralateral CTR, illustrates how FCTS can progress to involve both upper extremities, increasing the risk for permanent nerve damage if not appropriately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Phalen's test was positive at the most small FCTS case series have been published. However, essentially all of these studies lack outcome measures beyond five years postoperatively [2,4,[8][9][10][11][12]. In addition, there are few reports noting outcomes in children afflicted with this condition.…”
Section: Journal Of Aesthetic and Reconstructive Surgery Issn 2472-1905mentioning
confidence: 99%
“…While CTS is associated with a number of systemic diseases and some mechanical and occupational factors (Mattioli et al 2009;Uchiyama et al 2010), a genetic predisposition for CTS has also been shown (Hakim et al 2002;Lozano-Calderon et al 2008). CTS presenting in childhood should prompt consideration of an underlying lysosomal storage disorder or other genetic condition (Van Meir and De Smet 2003;Sri-Ram et al 2007;Yuen et al 2007). Patients presenting to Australian general practice with symptoms of CTS are predominantly female (male-female ratio 2 : 3) and 46% are aged 45-65 years (Charles et al 2009).…”
Section: Discussionmentioning
confidence: 99%